Deficiencies in both starch synthase IIIa and branching enzyme IIb lead to a significant increase in amylose in SSIIa-inactive japonica rice seeds - Asai, Hiroki (Oxford University Press, 2014)
Starch synthase (SS) IIIa has the second highest activity of the total soluble SS activity in developing rice endosperm. Branching enzyme (BE) IIb is the major BE isozyme, and is strongly expressed in developing rice endosperm. A mutant (ss3a/be2b) was generated from wild-type japonica rice which lacks SSIIa activity. The seed weight of ss3a/be2b was 74–94% of that of the wild type, whereas the be2b seed weight was 59–73% of that of the wild type. There were significantly fewer amylopectin short chains [degree of polymerization (DP) ≤13] in ss3a/be2b compared with the wild type. In contrast, the amount of long chains (DP ≥25) connecting clusters of amylopectin in ss3a/be2b was higher than in the wild type and lower than in be2b. The apparent amylose content of ss3a/be2b was 45%, which was >1.5 times greater than that of either ss3a or be2b. Both SSIIIa and BEIIb deficiencies led to higher activity of ADP-glucose pyrophosphorylase (AGPase) and granule-bound starch synthase I (GBSSI), which partly explains the high amylose content in the ss3a/be2b endosperm. The percentage apparent amylose content of ss3a and ss3a/be2b at 10 days after flowering (DAF) was higher than that of the wild type and be2b. At 20 DAF, amylopectin biosynthesis in be2b and ss3a/be2b was not observed, whereas amylose biosynthesis in these lines was accelerated at 30 DAF. These data suggest that the high amylose content in the ss3a/be2b mutant results from higher amylose biosynthesis at two stages, up to 20 DAF and from 30 DAF to maturity.